2016
DOI: 10.1016/j.jmii.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

SNP rs4331426 in 18q11.2 is associated with susceptibility to tuberculosis among female Han Taiwanese

Abstract: A single nucleotide polymorphism (SNP) rs4331426 located in a gene-poor region on chromosome 18q11.2 has been associated with tuberculosis (TB) by genome-wide association studies in Ghana and Gambia. In this study, we analyzed the SNP rs4331426 for its association with the risk of TB in the Taiwanese population. The SNP rs4331426 was genotyped in a case-control design that included 377 Han Taiwanese (200 TB patients and 177 controls) and was associated with TB (marginally significant p = 0.078). An increasingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…However, no report has indicated that this genotype is related to regulation of IFI16 gene expression and the development of disease. Similar to previous studies in the Han Taiwanese population, SOCS3 SNPs rs4331426 in women and rs35037722 in men were associated with TB 6,34 and NLRP3 SNPs rs3806268 and rs34298354 in women and TLR2 SNP rs3804100 in men were associated with MAC 33 . In addition, bisphenol A, an environmental estrogen, stimulates IFI16 protein expression in human peripheral blood mononuclear cells 35 , suggesting a possible gender-dependent association of IFI16 gene polymorphism with TB risk.…”
Section: Discussionsupporting
confidence: 87%
“…However, no report has indicated that this genotype is related to regulation of IFI16 gene expression and the development of disease. Similar to previous studies in the Han Taiwanese population, SOCS3 SNPs rs4331426 in women and rs35037722 in men were associated with TB 6,34 and NLRP3 SNPs rs3806268 and rs34298354 in women and TLR2 SNP rs3804100 in men were associated with MAC 33 . In addition, bisphenol A, an environmental estrogen, stimulates IFI16 protein expression in human peripheral blood mononuclear cells 35 , suggesting a possible gender-dependent association of IFI16 gene polymorphism with TB risk.…”
Section: Discussionsupporting
confidence: 87%
“…The OR analysis showed a sex-dependent association of the rs13170556 TC genotype with TB risk. Sex-dependent associations of rs4331426 and rs35037722 with TB risk have been reported previously, similar to studies in the Han Taiwanese population [ 3 , 33 ]. The GTExPortal database indicates an association of rs13170556 with HAVCR2 expression in testis tissue ( https://gtexportal.org/home/snp/rs13170556 ) [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, these SNPs were not associated with TB . In contrast, SNP rs4331426A/G was in a case–control study (200 TB patients, 177 controls) associated with TB in the Han Taiwanese population . A subsequent meta‐analysis of SNP rs4331426A/G at 18q11.2 included five studies in Chinese populations with a total of 3118 cases and 3226 control and showed that variant rs4331426A/G was also not associated with TB .…”
Section: Candidate Gene Studies In Tuberculosismentioning
confidence: 97%